Fundamental study of waste oil potential as base oil alternative in grease formulation - N. Suhaila, A. Japar; Mohd Aizudin, Abd Aziz; Mohd Najib, Razali (2018)
Large consumption of crude oil in lubrication industry might adversely affected by the reduction of crude oil production due to the decline of petroleum reserves. Environmental pollution caused by the improper disposal of waste oils and the recyclability of waste oils has brought interest to study the potential use of the waste oils. The main purposes of the current research were to formulate grease using different types of base oils from waste oils and to study the grease structure formation ability. Waste lubricating oil (WLO), spent hydraulic oil (WHO) and used brake oil (WBO) were used as base oils. Sodium hydroxide and molybdenum disulfide were used as thickener and additive. The formulated greases were studied by observing the grease’s appearance and measuring the oil separation during storage. The overall results show that the formulated greases have achieved the desired grease structure of semisolid form using WLO and WHO as base oil with oil separation up to 10%.